Immunoglobulin V(H) usage during primary infection of rhesus monkeys with chimeric simian-human immunodeficiency viruses. - Margolin, D H (1997)
It has been suggested that naive immunoglobulins encoded by the V(H)3 gene family interact aberrantly with human immunodeficiency virus type 1 (HIV-1) gp120 via a superantigenic epitope, causing initial expansion and eventual depletion of V(H)3-expressing B cells. However, this possibility has not been prospectively assessed during an AIDS virus infection. We determined V(H) family usage in rhesus monkeys during primary infection with chimeric viruses expressing HIV-1 envelopes on a simian immunodeficiency virus (SIVmac) backbone (SHIVs). Four SHIVs with different envelopes and pathogenicities were studied. V(H) family usage was prospectively assessed in peripheral blood mononuclear cells and lymph node cells of these monkeys by a semiquantitative PCR technique. In the first months following SHIV infection, a period of intense viral antigenemia, representation of various V(H) families increased or decreased for individual monkeys, but no single V(H) family was consistently altered. In particular, the average representation of V(H)3-bearing B lymphocytes did not change. This observation suggests that the envelope glycoprotein of HIV-1 does not selectively expand or deplete the V(H)3 repertoire of primate B cells during acute AIDS virus infection, contrary to predictions of the gp120 superantigen hypothesis.